Authority, gender, and midwifery in early modern Italy : contested deliveries - Kosmin, Jennifer F. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Authority, Gender, and Midwifery in Early Modern Italy: Contested Deliveries explores attempts by church, state, and medical authorities to regulate and professionalize the practice of midwifery in Italy from the late sixteenth to the late eighteenth century. Medical writers in this period devoted countless pages to investigating the secrets of women's sexuality and the processes of generation. By the eighteenth century, male practitioners in Britain and France were even successfully advancing careers as male midwives. Yet, female midwives continued to manage the vast majority of all early modern births. An examination of developments in Italy, where male practitioners never made successful inroads into childbirth, brings into focus the complex social, religious, and political contexts that shaped the management of reproduction in early modern Europe. Authority, Gender, and Midwifery in Early Modern Italy argues that new institutional spaces to care for pregnant women and educate midwives in Italy during the eighteenth century were not strictly medical developments but rather socio-political responses both to long standing concerns about honor, shame, and illegitimacy, and contemporary unease about population growth and productivity. In so doing, this book complicates our understanding of such sites, situating them within a longer genealogy of institutional spaces in Italy aimed at regulating sexual morality and protecting female honor. It will be of interest to scholars of the history of medicine, religious history, social history, and Early Modern Italy.
OCLC-licensed vendor bibliographic record.
Keywords: Midwifery -- Italy -- History; Midwives -- Italy -- History; Childbirth -- Religious aspects; Childbirth -- Political aspects -- Italy -- History; HISTORY / Europe / Italy; HISTORY / Modern / 18th Century